2019
DOI: 10.1016/j.meegid.2019.103939
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and genomic characteristics of bovine kobuvirus from dairy calves in China

Abstract: A B S T R A C TIn this study, 96 diarrheic and 77 non-diarrheic fecal samples from dairy calves were collected from 14 dairy farms in 4 provinces to investigate the molecular prevalence and genomic characteristics of Bovine Kobuvirus (BKoV) in China. The results showed that the BKoV positive rate for the diarrheic feces (35.42%) was significantly higher than that for the non-diarrheic feces (11.69%, p < 0.001). Interestingly, three potential novel VP1 lineages were identified from 15 complete VP1 sequences, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 15 publications
3
19
0
Order By: Relevance
“…Similar to findings reported byLi et al, 2019, these 121 strains form 8 lineages. BKV strains from UK belongs to two lineages (1 and 5), whereas BKV strains from China are lineage 2, 3, 4, 6, 7 and 8.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…Similar to findings reported byLi et al, 2019, these 121 strains form 8 lineages. BKV strains from UK belongs to two lineages (1 and 5), whereas BKV strains from China are lineage 2, 3, 4, 6, 7 and 8.…”
supporting
confidence: 83%
“…positive out of 49) (Park et al, 2010). Two studies were also performed in China (Chang et al, 2014;Li et al, 2019) (Table 1). The first study reported detection of BKV in 58 of 166 faecal samples collected in diarrhoeic dairy cows (Chang et al, 2014).…”
Section: Rt-pcr Detection Of Bkv In Asian Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact role of BKV in the pathogenesis of diarrhea is not fully elucidated; however, the detection rate of BKV in fecal samples from calves with clinical signs is higher when compared with animals without clinic signs, reinforcing the participation of BKV in the pathogenesis of diarrhea [35]. In this study, BKV was identified in mixed infections, and similar findings were previously described [21,36], suggesting that the occurrence of this virus may be associated with the concomitant presence of other diarrheic pathogens of cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Kobuviruses have a wide host range worldwide, including humans, dogs, cats, pigs, cattle, goats, sheep, bats, rats, and mice [1,4,[8][9][10]. The mouse kobuvirus was detected in Peromyscus crinitus and Peromyscus maniculatus mice in the USA in 2011 [11].…”
Section: Introductionmentioning
confidence: 99%